Mediated immediacy: constructing authentic testimony in audio-visual media. Issue 2 (3rd April 2017) - Jones, Sara
Abstract: The article argues that the power of witnessing is intimately linked to concepts of authenticity – it is the eyewitness who, it is believed, can truly give an account of 'what it was really like'. However, in order to ensure an impact on memory cultures, witness testimony must be recorded and fixed in a way that allows wider distribution. Such mediation can result in a perceived reduction in the authenticity of the narrative, as the person-to-person contact is lost. The recipient of the testimony is necessarily at a greater distance from the witness spatially and temporally than he or she would be in 'live' conversation. The article explores the methods deployed in audio-visual media (video testimony, memorial museums and documentary film) to lend authority and authenticity to the testimonies they record. In the process, it elaborates two theoretical terms: complementary authenticities and mediated remembering communities, which have broad significance for our understanding of how first-person testimony can have an impact on collective engagement with the past. The article concludes that such stagings of witness testimony in public and popular history are a powerful method of lending a strong emotive element to representations of past conflicts. This emotive element can connect individuals more closely to the victims of state and inter-communal violence, but may also prevent a deeper understanding of the societal causes and consequences of that violence, which is essential for processes of post-conflict reconciliation. In this way, the article makes a significant contribution to understanding the role of testimony and mediated authenticity in what might be termed the 'era of the postwitness'.